2020
DOI: 10.1177/0963689720903691
|View full text |Cite
|
Sign up to set email alerts
|

CORM-2 Pretreatment Attenuates Inflammation-mediated Islet Dysfunction

Abstract: During the process of human islet isolation a cascade of stressful events are triggered and negatively influence islet yield, viability, and function, including the production of proinflammatory cytokines and activation of apoptosis. Carbon monoxide-releasing molecule 2 (CORM-2) is a donor of carbon monoxide (CO) and can release CO spontaneously. Accumulating studies suggest that CORM-2 exerts cytoprotective and anti-inflammatory properties. However, the effect of CORM-2 on islet isolation is still unclear. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Here, we firstly demonstrated that FKBP5 inhibition by siRNAs or inhibitor SAFit2 activates the autophagy flux in inflammation cytokines treated β cells, which may facilitate β-cell survival under inflammation stress. In addition, inflammation is also a common stress for islet isolation [ 30 ]. In the ex vivo-cultured human islets and mice islets, we found that FKBP5 inhibition improved β-cell function, evidenced by the increased expression of β-cell functional genes NKX6.1 and PDX1 and by the enhanced glucose-stimulated insulin secretion, confirming the protective effect of FKBP5 in β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we firstly demonstrated that FKBP5 inhibition by siRNAs or inhibitor SAFit2 activates the autophagy flux in inflammation cytokines treated β cells, which may facilitate β-cell survival under inflammation stress. In addition, inflammation is also a common stress for islet isolation [ 30 ]. In the ex vivo-cultured human islets and mice islets, we found that FKBP5 inhibition improved β-cell function, evidenced by the increased expression of β-cell functional genes NKX6.1 and PDX1 and by the enhanced glucose-stimulated insulin secretion, confirming the protective effect of FKBP5 in β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we rstly demonstrated that FKBP5 inhibition by siRNAs or inhibitor SAFit2 activates the autophagy ux in in ammation cytokines treated β cells, which may facilitate β cell survival under in ammation stress. In addition, in ammation is also a common stress for islet isolation [31] . In the ex vivo cultured human islets and mice islets, we found that FKBP5 inhibition improved β cell function, evidenced by the increased expression of β cell functional genes NKX6.1 and PDX1 and by the enhanced glucose stimulated insulin secretion, con rming the protective effect of FKBP5 in β cells.…”
Section: Discussionmentioning
confidence: 99%
“…In furtherance of the use of CO gas in pancreatic islet transplantation, a very recent study shows that CO-RMs can produce the same salutary effects as CO gas. Pretreatment with 100 μM CORM-2 during islet isolation and subsequently transplanted (150 in number) into renal subcapsular space of STZ (165 mg/kg)-induced type 1 diabetic recipient mice resulted in significant downregulation of the expression of important proinflammatory genes such as TNF-α, interleukin-1beta (IL-1β), IL-6, intercellular adhesion molecule-1 (ICAM-1), Toll-like receptor 4 (TLR4), tissue factor (TF), chemokine ligand 2 (CCL2) and C-X-C motif ligand 10 (CXCL10) (Figure 1), which strongly correlated with markedly reduced apoptosis, improved islet cell viability, and higher glucose-stimulated insulin secretion and transplantation outcomes in comparison with control group (Cai et al, 2020). These findings suggest that treatment of islet grafts with CORM-2 at the beginning of isolation has the potential to protect the grafts in recipients from innate inflammation and apoptosis (two important factors that account for the progressive loss of islet function after transplantation in clinical practice) from the beginning of islet harvest through peri-transplant to post-transplant periods and could improve the quality and quantity of isolated human islets.…”
Section: Carbon Monoxide-releasing Molecules In Pancreatic Islet Transplantationmentioning
confidence: 98%
“…There is also non-metallic CO-RMs such as CORM-A1 (Motterlini et al, 2005b). Burgeoning evidence from preclinical studies shows that administration of CO-RMs during pancreatic islet isolation increases islet yields and insulin independence in type 1 diabetic transplant recipients (Nikolic et al, 2014;Nikolic et al, 2015;Cai et al, 2020). This minireview discusses current knowledge of CO gas and CO-RMs in preclinical pancreatic islet transplantation and underlying molecular mechanisms that ensure islet protection during isolation, islet culture, transplantation and post-transplant periods.…”
Section: Introductionmentioning
confidence: 99%